Pemphigoid gestationis: A Moroccan study - Chakiri Radia; Gallouj Salim; Inani Kawtar; Mernissi Fatima Zahra; Harmouch Taoufiq (Our Dermatology Online, 2017)
Introduction: Pemphigoid gestationis (PG) is a rare autoimmune skin disorder that occurs during pregnancy. Materials and Methods: Prospective study including all cases of PG diagnosed between 2010 and 2015. Results: We reported 16 patients: 12 multiparous and 4 primiparous, the average age was 30.43 years. The onset of the disease was done in 43.75% of cases at 3 trimester, and 25% of the 2 trimester with three cases of early post partum and post abortum cases. All patients had urticarial papules, vesicule were found in 85.7%. The beginning was done in periumbilical 62.5%. Histology objectified in all cases a sub epidermal detachment, and the IFD performed in 8 cases, objectified in 6 patients a linear deposit of C3 along the dermoepidermal junction. All patients were treated with Bethametasone at 30 g/d with a progressive degression over several months. Concerning the fetal prognosis we found two cases of prematurity, and one case of fetal death. One patient had a choriocarcinoma complicated molar pregnancy. Conclusion: All our patients evolved well under topical corticosteroids of very strong class, even with extensive lesions, so suggesting their first-line use, avoiding the recourse to the oral corticotherapy.